IMPERIALISM AND THE INEVITABILITY OF GLOBAL TERRORISM: AN OVERVIEW OF THE ROLE OF THE UNITED STATES OF AMERICA IN THE FIGHT AGAINST I.S.I.S. IN SYRIA: ANY LESSON FOR NIGERIA?* - Tal, Mohammed Kwarah (IJRDO - Journal of Social Science and Humanities Research, 2019)
The capitalist social order is no doubt one of the springboards of imperialism. As a predator, it swoops on weak nations mainly for its economic, political or strategic interests. Therefore, imperialism is not a policy but a necessary condition for the survival of the capitalist system. The Syrian crisis and terrorist activities are manifestations of imperialists’ impulses. This study explored the unvarnished motivations for imperialists’ activities and unmasked the underhand motives of the United States (U.S.) in its so-called war on terror, particularly its role in the Syrian crisis. Failure to make a puppet of President Bashar Al Assad by the U.S. and its allies necessitated the need for “regime change.” The intervention of Russia dramatically changed the power equation in favour of President Assad. It is becoming glaringly clear that the American Central Intelligence Agency (CIA) mission in Syria is heading towards failure. The Paper submits that with President Vladimir Putin in the driver’s seat, the Obama administration seems to be groping for a face-saving exit route via a political solution to the crisis. It argues Nigeria could face the same situation with Syria since it is highly endowed with natural resources such as oil and gas, and currently facing the challenge of Boko Haram, a group that has openly declared allegiance to Islamic State In Syria (ISIS). The Paper cautions the President Muhammadu Buhari administration and indeed Nigerians to be wary of the U.S. in its offer to assist Nigeria in fighting the Boko Haram the insurgents. The capitalist social order is no doubt one of the springboards of imperialism. As a predator, it swoops on weak nations mainly for its economic, political or strategic interests. Therefore, imperialism is not a policy but a necessary condition for the survival of the capitalist system. The Syrian crisis and terrorist activities are manifestations of imperialists’ impulses. This study explored the unvarnished motivations for imperialists’ activities and unmasked the underhand motives of the United States (U.S.) in its so-called war on terror, particularly its role in the Syrian crisis. Failure to make a puppet of President Bashar Al Assad by the U.S. and its allies necessitated the need for “regime change.” The intervention of Russia dramatically changed the power equation in favour of President Assad. It is becoming glaringly clear that the American Central Intelligence Agency (CIA) mission in Syria is heading towards failure. The Paper submits that with President Vladimir Putin in the driver’s seat, the Obama administration seems to be groping for a face-saving exit route via a political solution to the crisis. It argues Nigeria could face the same situation with Syria since it is highly endowed with natural resources such as oil and gas, and currently facing the challenge of Boko Haram, a group that has openly declared allegiance to Islamic State In Syria (ISIS). The Paper cautions the President Muhammadu Buhari administration and indeed Nigerians to be wary of the U.S. in its offer to assist Nigeria in fighting the Boko Haram the insurgents.